2021
DOI: 10.3390/hemato2030039
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Spontaneous Stress-Induced In Vitro Apoptosis of Human Acute Myeloid Leukemia Cells; Focus on Patient Heterogeneity and Endoplasmic Reticulum Stress

Abstract: In vitro culture is widely used for characterization of primary human acute myeloid leukemia (AML) cells, but even when using optimized handling and culture conditions the AML cells show spontaneous in vitro apoptosis with a gradual decrease in cell viability during culture. The extent of this stress-induced apoptosis varies between patients, and a high degree of apoptosis is associated with high pre-culture BCL2 levels together with low levels of BAX and Heat Shock Proteins 30 and 90. We compared the global p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…All samples were cryopreserved according to the same highly standardized protocol [128] and samples were stored in liquid nitrogen for the whole storage period. The duration of the storage period did not differ significantly for cells with and without NPM1-Ins, and the procedures for thawing and lysate preparation were highly standardized as described previously [25,[129][130][131][132][133][134][135]. Furthermore, in our previous study, the general quality of our proteomic data was confirmed by additional Western blot analyses of two differentially expressed proteins (CDK2, ERK1/2) and three differentially expressed phosphosites (CDK2T160, ERK1/2T202, ERK1/2 Y204).…”
Section: Patients and Sample Collectionmentioning
confidence: 76%
“…All samples were cryopreserved according to the same highly standardized protocol [128] and samples were stored in liquid nitrogen for the whole storage period. The duration of the storage period did not differ significantly for cells with and without NPM1-Ins, and the procedures for thawing and lysate preparation were highly standardized as described previously [25,[129][130][131][132][133][134][135]. Furthermore, in our previous study, the general quality of our proteomic data was confirmed by additional Western blot analyses of two differentially expressed proteins (CDK2, ERK1/2) and three differentially expressed phosphosites (CDK2T160, ERK1/2T202, ERK1/2 Y204).…”
Section: Patients and Sample Collectionmentioning
confidence: 76%
“…As described in a recent review, endocan is expressed mainly in lung and renal vasculature, but it is not restricted to endothelial expression and has been detected in normal serum as well as in several actively proliferative normal and malignant tissues [19,33,34]. A previous study described expression of endocan in AML and ALL blasts [35], but endocan did not reach quantifiable levels in previous proteomic studies of AML secretome, AML cell lysates, MSC secretome, MSC lysates, osteoblast secretome, or osteoblast lysates [36][37][38][39][40][41]. However, acute leukemia is characterized by increased angiogenesis, i.e., endothelial proliferation (see Section 4).…”
Section: Bone Marrow Expression Of Endocanmentioning
confidence: 99%
“…Proteomic and phosphoproteomic profiles were available for a consecutive subset of 15 younger AML patients (below 60 years of age), and we compared two contrasting patient groups with an antiproliferative effect corresponding to a relative response (i.e., the proliferation in the presence of bafilomycin A 10 nM being) <0.30 versus >0.60, respectively. These comparisons therefore included eight strong responders (Tables S1 and S2; patients 5,15,55,59,64,69,71) and seven weak responders (Table S1, patients 2, 23,31,34,36,41,51,73).…”
Section: Aml Cell Proliferation: Possible Protein Biomarkers For Susc...mentioning
confidence: 99%
“…Previous studies have demonstrated that cryopreserved AML cells usually include at least 70% viable cells (Annexin V − PI − ) together with minor subsets of early apoptotic (Annexin + PI − ) and late apoptotic/necrotic cells (Annexin V + PI + ) immediately after thawing [40]. During the first days of in vitro culture, cryopreserved AML cells undergo spontaneous or stress-induced in vitro apoptosis mainly due to chaperon-induced apoptosis [40,69]. There is a wide variation between patients with regard to the degree of spontaneous apoptosis during culture.…”
Section: Apoptosis Regulation: V-atpase Inhibition Decreases the Viab...mentioning
confidence: 99%